The medieval Nile : route, navigation, and landscape in Islamic Egypt - Cooper, John P. (Cairo ; New York : The American University in Cairo Press, 2014)
"An interdisciplinary study that draws together geography, historical navigation data, and eyewitness accounts into a comprehensive picture of one of the world's great rivers. This ground-breaking view of the navigational landscape of the Nile in medieval Egypt draws on a broad range of sources: medieval Arabic geographies; traveler accounts; archaeology; and meteorological, hydrological, and geological studies. John Cooper first charts the changing geography of the Nile waterways, particularly in the Delta, from the eve of Islam to the early modern period, and logs the 'rise and fall' of these waterways for natural and/or anthropogenic reasons. He then presents a new perspective on the Nile, drawing on traveler accounts and environmental data to portray the river as a uniquely challenging and sometimes dangerous navigational environment requiring extensive local knowledge by skilled and hard-working Nile navigators. Finally, he looks at how the main Delta and Red Sea ports of medieval Egypt fitted into the navigational landscape described, explaining how these ports were affected by changes occurring to the navigational landscape, and how they reflected the navigational conditions of the Nile and surrounding seas"--From the publisher.
Includes bibliographical references (pages 377-407) and index.
Keywords: 1250 - 1882; Navigation -- Nile River -- History; Landscape changes -- Nile River Region -- History; Waterways -- Egypt -- History; Navigation; Nile River -- History; Nile River -- History -- Sources; Nile River -- Geography; Nile River -- Environmental conditions; Egypt -- History -- 1250-1517.; Egypt -- History -- 1517-1882.; Egypt; Nile River; History